Medical education and patients' responsibilities: back to the future?. Issue 2 (30th January 2008) - Draper, H; Ives, J; Parle, J; Ross, N
Abstract : Medical student learning is dependent on an unwritten agreement between patients and the medical profession, in which students "practise" upon real patients in order that, when they are doctors, those same patients will benefit from the doctors' skills. Given the increasing propensity for patients to refuse to take part in such learning, there is a danger that doctors will qualify without being truly competent. As patients, we must all ask ourselves, when asked to take part in medical teaching: if this student/trainee doesn't learn now, on me and under supervision, how will the person be truly competent next time, when this is for real, and the patient might be me or my loved one? We argue that a new and more explicit agreement is needed, in which the default should be that all patients are willing to help in the education of medical students, while we ensure that all such students are already competent in simulation before first practising upon real patients.